Comparative assessment of factors affecting anxiety levels among adults attending online meditation sessions during the COVID-19 pandemic: A cross-sectional study - Anjali Pal; Sunil Kumar Panigrahi; Sagarika Majumdar (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: The ongoing coronavirus disease 2019 (COVID-19) pandemic induced the governments around the world to impose harsher preventive measures like stay at home order, lock down etc., to contain the spread of infection. This measure increased the stress of the general population through isolation of masses, loss of employment, and loss of recreation. There is a dearth of quality data showing anxiety levels among the population and association of novel nonpharmaceutical measures such as online meditation with it. MATERIALS AND METHODS: The study is a cross-sectional comparative study based on an online survey. The study population included 74 adult participants, out of which 30, included in the study group were attending structured online meditation sessions and 44 of the participants as a comparison group after matching age, gender, location of residence, and socioeconomic status. The data was collected using self-administered questionnaire. Multiple logistic regression was applied to ascertain factors contributing to the anxiety levels of the participants. RESULTS: Both the groups of participants were comparable in terms of their demographic characteristics. The mean generalized anxiety disorder (GAD 7) score among the participants of online meditation program was significantly lower as compared to those not attending any online meditation. 6.7% of the participants of online meditation had GAD 7 score more than 10 as compared to 13.6% among the comparison group (P value 0.7). CONCLUSION: "At home" mental health promotion measures such as structured online meditation can serve an important role in mitigating the mental health impact of COVID-19 pandemic on the community. Further researches are needed to assess the feasibility and effectiveness of such measures.